Pendekatan Tafsir Muhammad bin Abdul Wahhab: Metode, Dinamika, dan Pengaruh terhadap Pemikiran Islam Kontemporer - Khaerussalam, Ahmad; Ihsan, Muhamad Wuddy Agnia (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2026)
This study explores the methods and interpretive dynamics of Muhammad bin Abdul Wahhab in relation to the Qur’an, which formed one of the foundations of the Wahhabi movement in the 18th century. His tafsir is characterized by a literalist-textualist approach and a strong emphasis on the purity of tawhid (monotheism). The research analyzes this approach through an examination of his works, including Kitab al-Tawhid and Tafsir Surat al-Fatihah. It employs a qualitative-descriptive method with a library research approach and content analysis. The findings indicate that Muhammad bin Abdul Wahhab’s method of interpretation prioritizes a literal understanding of Qur’anic verses within a strict tawhid framework, a rejection of excessive allegorical interpretation (ta’wil), and the use of authentic hadiths as primary references. This approach significantly contributed to the development of Islamic reform movements in various parts of the world, including Indonesia. However, it has also sparked controversy due to its limited contextual comprehension and lack of openness to diverse Qur’anic interpretations. Thus, this paper offers a more comprehensive understanding of Muhammad bin Abdul Wahhab’s tafsir methodology and its relevance within the context of contemporary Islamic thought.